Study the Feasibility of Alumina for the Adsorption of Metal Ions from Water - A. Alnajar, Jenan; A. Kwaeri, Asawer; H. Sayhood, Ramzi; H. Slaymon, Abbas (Iraqi Journal of Chemical and Petroleum Engineering, 2014)
The present work describes the adsorption of Ba2+ and Mg2+ions from aqueous solutions by activated alumina in single and binary system using batch adsorption. The effect of different parameters such as amount of alumina, concentration of metal ions, pH of solution, contact time and agitation speed on the adsorption process was studied. The optimum adsorbent dosage was found to be 0.5 g and 1.5 g for removal of Ba2+ and Mg2+, respectively. The optimum pH, contact time and agitation speed, were found to be pH 6, 2h and 300 rpm, respectively, for removal of both metal ions. The equilibrium data were analyzed by Langmuir and Freundlich isotherm models and the data fitted well to both isotherm modes as indicated by higher correlation of determination R2> 0.87 in both single and binary systems. Pore diffusion model for batch adsorption was used to predict the concentration decay curve for adsorption of Ba2+ and Mg2+ onto activated alumina. There was a good agreement between the experimental data and the predicted decay curves using pore diffusion model.